How to Communicate Change. (12th August 2020) - Whelan, Jonathan
Abstract: Visualisation is an incredibly powerful tool for communicating business change. Our perception of the world is overwhelmingly visual, with 50% of our mental energy typically spent on processing this information, writes Jonathan Whelan FBCS.